Li‐Ion Batteries: Ultrafine Copper Nanopalm Tree‐Like Framework Decorated with Iron Oxide for Li‐Ion Battery Anodes with Exceptional Rate Capability and Cycling Stability (Adv. Energy Mater. 13/2019). Issue 13 (4th April 2019) - Seok, Jae Young; Lee, Jaehak; Park, Jung Hwan; Yang, Minyang
Abstract : In article number1803764, Minyang Yang and co‐workers report a 3D palm tree‐like Cu nanoframework (Cu NPF) with an ultrafine diameter and elongated branches for Li‐ion battery anodes. The hierarchical structural properties of Cu NPF provide simultaneous high surface area, electrical conductivity, and moderate porosity, thus enhancing overall electrochemical kinetics during the charge‐discharge. Of particular note, this electrode enables quick‐charging without capacity fading using iron oxide (Fe2 O3 ) as an active material.